Analisis Perbandingan Output Daya Listrik Mobile Photovoltaic Station Statis Dengan Single Axis Solar Tracking - Raftonado Situmorang; Muhammad Ridho Dewanto; Thorikul Huda; Kholiq Deliasgarin (LPPM Universitas Abdurrab, 2026)
Energy-efficient power sources are something that the government is promoting for implementation in the future. The increasing demand for environmentally friendly, mobile, and portable power sources requires a solution. This study explores the design and implementation of a mobile photovoltaic charging station, which aims to provide an environmentally friendly and efficient power source for electric vehicles and all light electrical appliances, such as those used in households and carpentry. This research began with the design and functional testing of the device. This charging station utilizes a 500-Watt Peak (WP) solar panel, a 12V 100 Ah deep-cycle lead-acid battery, and a 400-W up to 220V pure sine-wave inverter to support an average load of 300 Wh, lasting at least 1.5 hours when fully charged. After successful operation, the device collected 7 daily data points for comparison with previous data, allowing the effectiveness of the Mobile Photovoltaic Station with Single Axis Solar Tracking to be evaluated. The results of the study show that Mobile Photovoltaic Stations with Single Axis Solar Tracking generate 37.97% more electricity than static Photovoltaic Stations. These findings are expected to contribute to the development of sustainable mobile charging infrastructure, addressing critical needs in a rapidly evolving technological and environmental landscape.